Makna Bentuk dan Aksara Rerajahan - Simrana, I Gede Wahyu; Mudra, I Wayan; Yudarta, I Gede; Ardini, Ni Wayan (Jurnal Bali Membangun Bali, 2023)
Purpose: The purpose of this paper is to analyze the meaning of the Rerajahan form and script which are closely related to Balinese Hindu religious rituals where Rerajahan is one of the cultural assets of the archipelago. Research method: This study uses a qualitative literary approach which is described in such a way according to the data obtained which in its elaboration contains the process of its meaning. Results and discussion: Rerajahan is a Balinese Hindu culture as a local genius. Balinese Hindus firmly believe that Rerajahan has magical properties. Rerajahan will be meaningless if it is not filled with inner energy and driven by deep belief as well, then Rerajahan will be an empty image and only contains aesthetics. Implication: The magical powers that can be elicited by the rerajahan are used for sacred purposes, namely for matters related to Hinduism, which are called Panca Yadnya.